Selective compounds enhance osteoblastic activity by targeting HECT domain of ubiquitin ligase Smurf1 - Zhang, Yuan (Oncotarget, 2016)
The HECT-type ubiquitin ligase Smurf1 (Smad ubiquitination regulatory factor-1) plays the prominent role in regulation of bone formation, embryonic development, and tumorigenesis by directing the ubiquitin-proteasomal degradation of specific targets. In contrast with RING-type E3s, the catalytic HECT domain of Smurf1 firstly binds to and then transfers ubiquitin (Ub) molecules onto the substrates. The Smurf1-Ub interaction is required for Smurf1 catalytic ligase activity to promote substrate degradation. However, so far specific regulators or compounds controlling Smurf1-Ub interaction and the ligase activity have not been identified. Here we report two small molecule compounds targeting Ub binding region of HECT domain interrupt Smurf1-Ub contact, inhibit Smurf1 ligase activity and stabilize BMP signal components Smad1/5 protein level. Furthermore, these compounds increase BMP signal responsiveness and enhance osteoblastic activity in cultured cells. These findings provide a novel strategy through targeting Smurf1 ligase activity to potentially treat bone disorders such as osteoporosis.